Pengaruh Pengendalian Intern, Gaya Kepemimpinan dan Komitmen Organisasi terhadap Kinerja Karyawan pada PT. Berkah Sapta Palma (BSP) - Ratna Ratna; Nadiatul Khoiroh; Desi Ulandari (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2022)
Changes in the organizational environment that are increasingly complex and competitiv, require every organization and company to be more responsive in order to survive and continue to grow. The aims of this research are (1) to find out whether internal control, leadership style and organizational commitmenthave an effect on organizational performance at PT. Berkah Sapta Salma (BPS) Muara Bulian. (2) To find out whether internal control affects the company’s performance at PT. Berkah Sapta Salma (BPS) Muara Bulian. (3) To find out whether the leadership style affects the company’s performance at PT. Blessings of Sapta Salma (BPS) Muara Bulian. (4) To find out whether organizational commitment affects the company’s performance at PT. Blessings of Sapta Salma (BPS) Muara Bulian. The data used are primary data obtained through questionnaires to emloyees of PT. Berkah Sapta Salma (BPS) M uara Bulian and the sample of this study were 80 respondents. The data analysis method used multiple linear regression analysis using SPSS.20 program. Overall, it can be concluded that if the variables of internal Control, Leadership Style and Organiztional Commitment simultaneously affect the company’s performance variables, the better the implementation of the variables of Internal Control, Leadership Style and Organizational Commitment, the better the company’s performance will be.